The development of condensing and freezing unit for a solar powered refrigerator - Hossain, Md. Forhad; Exell, Robert H.B.; Saunier, G.Y.; Walter, Despiegelaere, Ir.; Government of Norway (Bangkok : Asian Institute of Technology, 1981)
An ammonia-water intermittent absorption refrigerator with a 0.9 m2 flat plate solar collector and a flooded type evaporator has been constructed. The flat plate collector design has been modified to enhance the ammonia generation as early as possible in the morning. The flat plate solar collector containing 10.5 kgs of aqua-ammonia solution having 50% of ammonia in water is used. The flooded type evaporator is used and a box containing water surrounding the evaporator coil is used to make ice , 2 . 68 kgs of ice being produced obtained after one day's regeneration of ammonia by solar energy. During refrigeration the temperature of the ammonia drops to - 10°c. The overall solar coefficient of performance (cooling effect divided by the solar energy input) is 0.077.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Solar energy research; Refrigerators